2013
DOI: 10.1016/j.bpj.2013.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Analysis of the Rotation of F1-ATPase under High Hydrostatic Pressure

Abstract: F1-ATPase is the water-soluble part of ATP synthase and is an ATP-driven rotary molecular motor that rotates the rotary shaft against the surrounding stator ring, hydrolyzing ATP. Although the mechanochemical coupling mechanism of F1-ATPase has been well studied, the molecular details of individual reaction steps remain unclear. In this study, we conducted a single-molecule rotation assay of F1 from thermophilic bacteria under various pressures from 0.1 to 140 MPa. Even at 140 MPa, F1 actively rotated with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…To visualize the pressure-induced changes in the structure and function of biomacromolecules, we have developed a high-pressure microscope that enables us to acquire various microscopic images with high-resolution and sensitivity even when hydrostatic pressure is applied. , It revealed that applied pressure dynamically changes the motility of molecular motors such as kinesin, F 1 -ATPase, and bacterial flagellar motors. ,, Thus, in this study, using the high-pressure microscope, we investigated the pressure-induced morphological changes of tubulin-encapsulating giant liposomes. The results obtained demonstrate that the morphology of tubulin-encapsulating giant liposomes is reversibly and repeatedly controllable by regulating the polymerization and depolymerization of MTs inside the giant liposomes by changing the hydrostatic pressure, which means that MTs are an excellent motion device to develop an artificial motile cell model.…”
Section: Introductionmentioning
confidence: 99%
“…To visualize the pressure-induced changes in the structure and function of biomacromolecules, we have developed a high-pressure microscope that enables us to acquire various microscopic images with high-resolution and sensitivity even when hydrostatic pressure is applied. , It revealed that applied pressure dynamically changes the motility of molecular motors such as kinesin, F 1 -ATPase, and bacterial flagellar motors. ,, Thus, in this study, using the high-pressure microscope, we investigated the pressure-induced morphological changes of tubulin-encapsulating giant liposomes. The results obtained demonstrate that the morphology of tubulin-encapsulating giant liposomes is reversibly and repeatedly controllable by regulating the polymerization and depolymerization of MTs inside the giant liposomes by changing the hydrostatic pressure, which means that MTs are an excellent motion device to develop an artificial motile cell model.…”
Section: Introductionmentioning
confidence: 99%
“…The 120 ı step rotation can be divided into 80 ı substep triggered after ATP binding, and 40 ı substep triggered after ATP hydrolysis (Yasuda et al 2001). We conducted a singlemolecule rotation assay of F 1 from thermophilic bacteria under various pressures (Okuno et al 2013). Although the mechanochemical coupling mechanism of F 1 -ATPase has been well studied, the molecular details of individual reaction steps remain unclear.…”
Section: Single Molecule Analysis Of the Rotation Of F 1 -Atpasementioning
confidence: 99%
“…We conducted a singlemolecule rotation assay of F 1 from thermophilic bacteria under various pressures (Okuno et al 2013). This is strongly supported by results of a rotation assay using a mutant F 1 ("E190D) (Okuno et al 2013). When 120 MPa pressure was applied to the system, the rotary motion drastically changed.…”
Section: Single Molecule Analysis Of the Rotation Of F 1 -Atpasementioning
confidence: 99%
“…Conversely, the second generation is a popular method for commercial purposes. Recently, single‐cell analysis has attracted interest because it helps to reveal unclear mechanisms of cell functions [27–30] and can be successfully performed on small volumes befitting cells. The second generation is highly conducive to small‐volume measurements because it enables a disposable measurement process.…”
Section: Introductionmentioning
confidence: 99%